La fresque sur ciment : un renouveau artistique - Marine Bayle; Éléonore Gueit; Évelyne Darque-Ceretti; Matthieu Horgnies; Marc Aucouturier (In Situ)
The fresco painting technique has been widely used throughout history in the occidental world, in particular at the Roman period, and is known to be the most durable form of mural painting. The traditional technique consists in applying water-dispersed pigments on a fresh lime plaster, which later hardens through carbonation reaction. Following the invention of the Portland cement at the 20th century, some mural artists experimented a similar painting technique on cement plaster. Although the setting mechanisms of cement are different from lime, the cement frescoes present the same aspect and the same durability as the lime frescoes. The historical and practical aspects of the lime technique are well-documented, but the fundamental mechanisms responsible for the properties of a fresco surface have rarely been investigated and are still poorly understood. Based on analyses of frescoes from the early 20th century and on laboratory reconstitutions, this study brings new insight on the formation of a fresco surface.